Pendapatan Pinang di Kabupaten Tanjung Jabung Barat - Faisal Hamid; Erni Achmad; Zainul Bahri; Siti Hodijah; Nurhayani . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Pinang Batara, is the first superior variety of areca nut in Indonesia, which was released and inaugurated by the Minister of Agriculture through the Decree of the Minister of Agriculture Number: 199 / Kpts / SR.120 / 1/2013. The demand for seeds continues to increase, coming from several provinces and even from abroad. This momentum is utilized by several farmers to run the Pinang Batara nursery business, This study aims to provide an overview of: Profile, Nursery Business, and profits obtained by breeders from the Pinang Batara nursery business activities. The data used are primary data, secondary data and other relevant information. Period 2019-2024. The data analysis method used in this study is descriptive research analysis and quantitative analysis. The type of data used is quantitative data.